Diagnostic Challenges in Non-albicans Candida Bloodstream Infection in an Immunocompromised Patient: A Case Report - Valentine Hursepuny; Yunialthy Dwia Pertiwi; Utma Laela Warka; Nadyah; Baedah Madjid; Andi Rofian Sultan; Mochammad Hatta; Firdaus Hamid (Journal of Clinical Microbiology and Infectious Diseases, 2026)
Introduction: Candidemia has increased in recent years, leading to prolonged hospital stay, increased healthcare costs, and high mortality. Patients with underlying conditions such as malignancy and those requiring invasive medical devices are at higher risk of Candida bloodstream infection. Therefore, this study aims to describe a rare case of non-albicans Candida bloodstream infection in an immunocompromised patient, with emphasis on diagnostic challenges and clinical implications of discordant laboratory identification in guiding appropriate management. Case Description: A 48-year-old female with cervical cancer undergoing chemotherapy and hemodialysis via a right-thigh double-lumen catheter presented to the emergency department with prolonged vaginal bleeding, oliguria, nausea, and significant weight loss. Laboratory findings revealed leukocytosis and renal impairment. She received a combination of ceftazidime, moxifloxacin, and metronidazole in the ICU. The patient had multiple invasive devices, including intravenous catheters, parenteral nutrition, and urinary catheters. Blood culture performed on day 15 of hospitalisation identified Candida lipolytica, which was sensitive to voriconazole, amphotericin B, and flucytosine. Moreover, PCR and phylogenetic sequencing were performed to ensure accurate species identification. Despite the final identification and clinical management efforts, the patient’s clinical condition continued to deteriorate, and she eventually succumbed after three weeks of hospitalisation. Conclusion: This case highlights a rare non-albicans Candida bloodstream infection in an immunocompromised patient, emphasising the diagnostic challenges associated with accurate species identification. A stepwise diagnostic approach with culture, proteomic, and molecular confirmation, including PCR and phylogenetic analysis, is essential to ensure accurate identification and optimal clinical management.